Instagram Live Utilization for Health Education and Health Promotion during COVID-19 Pandemic - Mohammad Ainul Maruf; Muhammad Wiji Utomo; Syifa Nurfizri (Ikatan Ahli Kesehatan Masyarakat Indonesia Kota Tangerang Selatan, 2022)
The spread of COVID-19 has hampered face-to-face health education and health promotion activities, so that social media like Instagram has taken a bigger role. This study aims to analyze the use of the Instagram Live (IG live) feature for health education and promotion carried out by the Indonesian Public Health Association – South Tangerang City Board (IAKMI Tangsel) during the period of January to September 2021. The results showed that there were 11 IG live series content related to COVID-19 that were created, with the shortest duration being 20 minutes 3 seconds and the longest duration being 42 minutes 19 seconds. The most content was created in March and there were five months that had no content. The content with the most views, the most likes, the highest number of (follower and non-follower) accounts reached, and the greatest impression was the content that discussed the COVID-19 vaccination. Meanwhile, the content with the least views, the least likes, the lowest number of accounts reached, and the smallest impression was the content that discussed student initiatives during the pandemic. The results of this study are useful to be taken into consideration for future social media content plans.